2014
DOI: 10.1094/cchem-04-13-0068-r
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Kafirin Allelic Diversity, Starch Content, and Protein Digestibility on Ethanol Conversion Efficiency in Grain Sorghum

Abstract: Cereal Chem. 91(3):218-227Seed protein and starch composition determine the efficiency of the fermentation process in the production of grain-based ethanol. Sorghum, a highly water-and nutrient-efficient plant, provides an alternative to fuel crops with greater irrigation and fertilizer requirements, such as maize. However, sorghum grain is generally less digestible because of extensive disulfide cross-linking among sulfur-rich storage proteins in the proteinstarch matrix. Thus, the fine structure and composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…The 45-kDa oligomer is present in both the sorghum and maize prolamin profiles, but unlike in sorghum, the maize oligomer is susceptible to depolymerization by reducing agents both in cooked and uncooked samples (Nunes et al, 2005). Cremer et al (2014b) measured raw and cooked in vitro protein digestibility of three lines containing the b-kafirin null gene and reported that protein digestibility of the null lines was not different from other lines tested. In monomeric forms, kafirins are relatively readily digestible, with a-kafirin being the most easily digestible (Nunes et al, 2004), but because of its interior location within the protein body, a-kafirin is the last to be digested and the most abundant fraction in an undigested residual protein as demonstrated by in vitro digestion experiments (Oria et al, 1995b;Nunes et al, 2004) and transmission electron microscopy observations (Taylor et al, 1985a;Oria et al, 1995b).…”
Section: Kafirin Proteins and Sorghum Protein Digestibilitymentioning
confidence: 90%
See 2 more Smart Citations
“…The 45-kDa oligomer is present in both the sorghum and maize prolamin profiles, but unlike in sorghum, the maize oligomer is susceptible to depolymerization by reducing agents both in cooked and uncooked samples (Nunes et al, 2005). Cremer et al (2014b) measured raw and cooked in vitro protein digestibility of three lines containing the b-kafirin null gene and reported that protein digestibility of the null lines was not different from other lines tested. In monomeric forms, kafirins are relatively readily digestible, with a-kafirin being the most easily digestible (Nunes et al, 2004), but because of its interior location within the protein body, a-kafirin is the last to be digested and the most abundant fraction in an undigested residual protein as demonstrated by in vitro digestion experiments (Oria et al, 1995b;Nunes et al, 2004) and transmission electron microscopy observations (Taylor et al, 1985a;Oria et al, 1995b).…”
Section: Kafirin Proteins and Sorghum Protein Digestibilitymentioning
confidence: 90%
“…Grain sorghum protein digestibility is influenced by several factors, some of which are related to grain physicochemical properties, but is controlled, to a large degree, by kafirin composition and endosperm protein body structure (Hamaker et al, 1995;Oria et al, 2000;Duodu et al, 2002Duodu et al, , 2003Bean et al, 2011;Cremer et al, 2014b). In other words, protein structure, composition, and protein-protein interactions have far greater influence on sorghum protein digestibility than nonprotein factors and protein-nonprotein interactions.…”
Section: Kafirin Proteins and Sorghum Protein Digestibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Chip profiles indicate that several cultivars in addition to the β-kafirin null mutants contain relatively low levels of β-kafirin, including 296B, a highly digestible line (189). LOC analysis also revealed the presence of a small peak visible at 46kDa in alcohol-soluble samples, which could represent a high Mw kafirin or kafirin dimer.…”
Section: Lab On Chip (Loc) Analysis Of Storage Proteinsmentioning
confidence: 98%
“…S2) protein fractions across 28 sorghum lines using RP-HPLC revealed a range of diversity, particularly in the alcoholsoluble kafirin-containing fraction. Variation observed across wild-type and mutant lines could contribute to phenotypic differences, such as increased flour viscosity and fermentation efficiency (188,189). Among the β-kafirin null lines QL12, IS17214 and RTx2737, a high degree of similarity was observed in the alcohol-soluble peak distributions compared to lines with functional β-kafirin…”
Section: Rp-hplc Profiling Of Grain Proteinsmentioning
confidence: 99%